GREENING UZBEKISTAN: STRATEGIES FOR A SUSTAINABLE FUTURE - Shayusupova Lobar Rixsievna; Khasanov Azizjon Akhro Ugli (PT ANTIS International Publisher, 2024)
: This article examines the critical need for Uzbekistan to expedite its transition to a green economy. The research highlights the severe risks posed by delaying this transition, including significant economic losses from land degradation and dust storms, high carbon and energy intensity, and the potential lock-in of outdated technologies. Uzbekistan's government has already initiated the